PEMENUHAN HAK-HAK PERLINDUNGAN ANAK (STUDI PERBANDINGAN HUKUM POSITIF DAN HUKUM TATA NEGARA ISLAM) - Ocha Juliennelzky; Hidayati Fitri; Dian Pertiwi (JISRAH: Jurnal Integrasi Ilmu Syariah, 2023)
The results of the author's research in this study that the fulfillment of chidren's rights in positive law is fully regulated by law in which it is regulated explicitly and clearly both the fulfillment of the rights of the child itself and the sanctions for violators. whereas in Islamic constitutional law, the fulfullment of children's rights is explained in the arguments of the Qur'an, hadith, compilations of Islamic law, and also MUI fatwas where are clear. but the similarity is that in positive law and Islamic constitutional law the fulfillment of children's rights is fully guarded and protected so that the child's life is safe and peaceful..